2021
DOI: 10.1021/acs.langmuir.1c01825
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Bacterial Quorum Sensing Signals with Model Lipid Membranes: Influence of Acyl Tail Structure on Multiscale Response

Abstract: Many common bacteria use amphiphilic N-acyl-Lhomoserine lactones (AHLs) as signaling molecules to coordinate group behaviors at high cell densities. Past studies demonstrate that AHLs can adsorb to and promote the remodeling of lipid membranes in ways that could underpin cell−cell or host−cell interactions. Here, we report that changes in AHL acyl tail group length and oxidation state (e.g., the presence or absence of a 3-oxo group) can lead to differences in the interactions of eight naturally occurring AHLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…Analogous fluorescence microscopy experiments to characterize the interactions of 3-oxo-C12-AHL (Figure B and Figure S6C) with these DOPE-containing bilayers revealed the immediate and apparently direct formation of hemispherical caps on the surfaces of the bilayers; that is, we did not observe these caps to form by the initial formation and subsequent retraction of extended tubule structures. The introduction of 3-oxo-C12-HS at a concentration of 50 μM (Figure F and Figure S6C) appeared to lead to the formation of hemispherical caps that appeared to protrude more from the surface of the bilayer than those reported in our previous studies. ,, Additional studies will be required to investigate possible differences in these structures more completely.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Analogous fluorescence microscopy experiments to characterize the interactions of 3-oxo-C12-AHL (Figure B and Figure S6C) with these DOPE-containing bilayers revealed the immediate and apparently direct formation of hemispherical caps on the surfaces of the bilayers; that is, we did not observe these caps to form by the initial formation and subsequent retraction of extended tubule structures. The introduction of 3-oxo-C12-HS at a concentration of 50 μM (Figure F and Figure S6C) appeared to lead to the formation of hemispherical caps that appeared to protrude more from the surface of the bilayer than those reported in our previous studies. ,, Additional studies will be required to investigate possible differences in these structures more completely.…”
Section: Resultsmentioning
confidence: 64%
“…We recently reported on the influence of AHL head- and tailgroup structure on membrane remodeling in single-component SLBs of DOPC formed using either a vesicle fusion or bicelle formation technique. Other groups have reported that it can be difficult to form some compositionally complex, mixed-lipid SLBs using the vesicle fusion technique , and that even single-component bilayers are often nonhomogeneous and can contain unruptured vesicles that appear as optical defects .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic functional luminescent materials have received much attention in recent years since they have exhibited a great research value in the fields of bioimaging, sensors, display, and information technology. In particular, it is worth noting that the emissive intensity or wavelength of the materials can be typically regulated through external stimulation such as pH, temperature, electricity, light, mechanical force, solvent polarity, and so forth, reflecting the switching behaviors of the functional molecules. Among these cases, the light-controlled molecular switch continues to be one of the most significant research motives because light does not easily produce additional byproducts in the system and can also be operated rapidly, accurately, and remotely. Generally, the principle of a light-controlled molecular switch is based on photochemical reactions, such as photocyclization and photoisomerization, and there are still few designs for molecular switches based on the conformational conversion. Thus, the reversibility of these switch systems needs an additional chemical or energy imposition. In contrast, several nonequilibrium systems based on the photoexcitation principle have been developed as autonomous photoswitches (resettable without a secondary stimuli), which can achieve self-recovery through relaxation when the light stimulation is cut off. However, the autonomous photoswitch can easily work in solution or in some well-defined crystalline systems. To create an autonomously photoswitchable material that can work in the solid state, even in the amorphous form, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%